2018
DOI: 10.1186/s13018-018-0892-0
|View full text |Cite
|
Sign up to set email alerts
|

The effects of graft shrinkage and extrusion on early clinical outcomes after meniscal allograft transplantation

Abstract: BackgroundGraft shrinkage or radial extrusion is a reported complication after meniscus allograft transplantation (MAT). Whether shrinkage or extrusion progress after surgery and whether they are associated with the clinical outcome of MAT remain debatable. In this study, graft shrinkage and extrusion were measured in the coronal and sagittal planes using serial postoperative magnetic resonance imaging (MRI). The purpose of this study was to evaluate if graft shrinkage or extrusion is correlated to the clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 39 publications
(36 reference statements)
1
15
0
Order By: Relevance
“…Extrusion did not correlate with the clinical outcomes when the follow-up time was short [28]. However, at the 5-year follow-up, reduced meniscus extrusion may lead to more favorable midterm outcomes after pullout fixation for MMPRTs [29].…”
Section: Discussionmentioning
confidence: 81%
“…Extrusion did not correlate with the clinical outcomes when the follow-up time was short [28]. However, at the 5-year follow-up, reduced meniscus extrusion may lead to more favorable midterm outcomes after pullout fixation for MMPRTs [29].…”
Section: Discussionmentioning
confidence: 81%
“…The study by Lee et al 8 showed a similar conclusion for shrinkage of the WPH and WMB, but no data for the WAH were available in his study. However, in the study by Kim et al 22 , no significant progression of shrinkage was observed between 3 and 12 months postoperatively. The reason for this effect might be that in Kim's study, shrinkage was calculated by multiplying the width and height of the three sections and adding these values together.…”
Section: Discussionmentioning
confidence: 83%
“…In our study, CGE and the CPRE increased with time but became steady after 2 years postoperatively; however, changes in the ACMD, APRE, PCMD and PCRE were more complicated but varied in a contrary manner, indicating that the sagittal locations of allografts were constantly changing. A study by Kim et al 22 showed that in the sagittal plane, the mean absolute ACMDs were 2.59 ± 1.75, 2.58 ± 1.85, and 2.37 ± 1.60 mm, and the mean relative ACMDs were 20.7% ± 13.1%, 20.6% ± 13.8%, and 19.0% ± 12.2% at the 3 follow-up time points. The mean absolute PCMDs were − 1.23 ± 3.34, − 1.28 ± 3.08, and − 1.42 ± 2.77 mm, and the mean relative PCMDs were − 10.3% ± 25.9%, − 11.0% ± 24.6%, and − 12.2% ± 23.2% at the same time points.…”
Section: Discussionmentioning
confidence: 95%
“…[2][3][4] This study, along with previously published long-term data, supports a lack of correlation between the degree of shrinkage and outcomes. 1,5,6 Conversely, it has been reported that there is a narrow anatomic window to place transplants anatomically without significantly altering the pressure distribution across the meniscus. 7 Nonanatomic placement of meniscal allografts has also been shown as a significant predictor for graft extrusion after lateral MAT.…”
Section: See Related Article On Page 2887mentioning
confidence: 99%